The feasibility of quantitative MRI of extra‐ocular muscles in myasthenia gravis and Graves' orbitopathy - Keene, Kevin R.; Vught, Luc; Velde, Nienke M.; Ciggaar, Isabeau A.; Notting, Irene C.; Genders, Stijn W.; Verschuuren, Jan J.G.M.; Tannemaat, Martijn R.; Kan, Hermien E.; Beenakker, Jan‐Willem M. (NMR in biomedicine, 2021)
Although quantitative MRI can be instrumental in the diagnosis and assessment of disease progression in orbital diseases involving the extra‐ocular muscles (EOM), acquisition can be challenging as EOM are small and prone to eye‐motion artefacts. We explored the feasibility of assessing fat fractions (FF), muscle volumes and water T2 (T2water) of EOM in healthy controls (HC), myasthenia gravis (MG) and Graves' orbitopathy (GO) patients. FF, EOM volumes and T2water values were determined in 12 HC (aged 22‐65 years), 11 MG (aged 28‐71 years) and six GO (aged 28‐64 years) patients at 7 T using Dixon and multi‐echo spin‐echo sequences. The EOM were semi‐automatically 3D‐segmented by two independent observers. MANOVA and t‐tests were used to assess differences in FF, T2water and volume of EOM between groups (P < .05). Bland–Altman limits of agreement (LoA) were used to assess the reproducibility of segmentations and Dixon scans. The scans were well tolerated by all subjects. The bias in FF between the repeated Dixon scans was −0.7% (LoA: ±2.1%) for the different observers; the bias in FF was −0.3% (LoA: ±2.8%) and 0.03 cm3 (LoA: ± 0.36 cm3) for volume. Mean FF of EOM in MG (14.1% ± 1.6%) was higher than in HC (10.4% ± 2.5%). Mean muscle volume was higher in both GO (1.2 ± 0.4 cm3) and MG (0.8 ± 0.2 cm3) compared with HC (0.6 ± 0.2 cm3). The average T2water for all EOM was 24.6 ± 4.0 ms for HC, 24.0 ± 4.7 ms for MG patients and 27.4 ± 4.2 ms for the GO patient. Quantitative MRI at 7 T is feasible for measuring FF and muscle volumes of EOM in HC, MG and GO patients. The measured T2water was on average comparable with skeletal muscle, although with higher variation between subjects. The increased FF in the EOM in MG patients suggests that EOM involvement in MG is accompanied by fat replacement. The unexpected EOM volume increase in MG may provide novel insights into underlying pathophysiological processes. MRI can play a role in the diagnosis and assessment of disease progression in orbital disease involving the extra‐ocular muscles. We explored the feasibility of quantitative MRI in extra‐ocular muscles in healthy controls, myasthenia gravis and Graves' orbitopathy patients. We found increases in muscle volume and fat fraction in these patients.